Sustainable Recovery of Lead from Secondary Waste in Chloride Medium: A Review - Vargas-Riquelme, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Environmental regulations on lead recycling are becoming increasingly stringent, prompting the search for sustainable alternatives to conventional high-temperature processes. Hydrometallurgical methods in chloride media have emerged as a viable option for recovering lead from mining and urban wastes, including lead anode corrosion residues, zinc leaching residues, and spent lead–acid batteries. This study reviews the key conditions for lead recovery in chloride media, highlighting the variables that optimize lead dissolution, and the potential challenges associated with these processes. The findings indicate that efficient lead recovery requires high chloride concentrations, with acidity playing a critical role depending on the relative concentrations of lead and sulfate in the solution. When lead and sulfate concentrations are similar, stable lead–chloride complexes form within a pH range of 0 to 6.0. However, at higher sulfate concentrations, the pH range narrows significantly to 0 to 2.0, necessitating a more acidic environment for effective dissolution. Chloride media offer a distinct advantage through the formation of stable lead–chloride complexes, whose stability is influenced by chloride concentration, sulfate concentration, pH, and redox potential. Moreover, this approach provides a sustainable alternative that could integrate seawater into industrial processes, particularly in regions facing water scarcity. © 2025 by the authors.